Ethnic quotas and unintended effects on women's political representation in Singapore. Issue 1 (January 2014) - Tan, Netina
This article examines the effects of ethnic quotas on women's political representation in Singapore. The 1988 electoral reform requires at least one minority ethnic candidate to be fielded in the multimember constituencies based on the party list plurality bloc vote system. Based on elite interviews, party publications and electoral data, this article argues that the increases in the district magnitude of the multimember constituencies have had the unintended effect of improving women's political participation. More broadly, the article shows the conditions under which electoral rules shape behaviour and focuses on how the ruling party leaders in Singapore act as gatekeepers through centralised candidate selection methods that have a direct impact on legislative diversity.